Binding of HIV-1 gp41-Directed Neutralizing and Non-Neutralizing Fragment Antibody Binding Domain (Fab) and Single Chain Variable Fragment (ScFv) Antibodies to the Ectodomain of gp41 in the Pre-Hairpin and Six-Helix Bundle Conformations - Louis, John M. (Public Library of Science, 2014)
We previously reported a series of antibodies, in fragment antigen binding domain (Fab) formats, selected from a human non-immune phage library, directed against the internal trimeric coiled-coil of the N-heptad repeat (N-HR) of HIV-1 gp41. Broadly neutralizing antibodies from that series bind to both the fully exposed N-HR trimer, representing the pre-hairpin intermediate state of gp41, and to partially-exposed N-HR helices within the context of the gp41 six-helix bundle. While the affinities of the Fabs for pre-hairpin intermediate mimetics vary by only 2 to 20-fold between neutralizing and non-neutralizing antibodies, differences in inhibition of viral entry exceed three orders of magnitude. Here we compare the binding of neutralizing (8066) and non-neutralizing (8062) antibodies, differing in only four positions within the CDR-H2 binding loop, in Fab and single chain variable fragment (ScFv) formats, to several pre-hairpin intermediate and six-helix bundle constructs of gp41. Residues 56 and 58 of the mini-antibodies are shown to be crucial for neutralization activity. There is a large differential (≥150-fold) in binding affinity between neutralizing and non-neutralizing antibodies to the six-helix bundle of gp41 and binding to the six-helix bundle does not involve displacement of the outer C-terminal helices of the bundle. The binding stoichiometry is one six-helix bundle to one Fab or three ScFvs. We postulate that neutralization by the 8066 antibody is achieved by binding to a continuum of states along the fusion pathway from the pre-hairpin intermediate all the way to the formation of the six-helix bundle, but prior to irreversible fusion between viral and cellular membranes.